Simulation Study on Strength and Failure Characteristics for Granite with a Set of Cross-Joints of Different Lengths. (13th March 2018) - Yin, Dawei; Chen, Shaojie; Liu, Xingquan; Ma, Hongfa
Abstract : The strength and failure characteristics for granite specimen with a set of cross-joints of different lengths were studied using PFC 2D software. The results show that when the included angle of α between the main joint and loading direction is 30° or 45°, no matter what the included angle of β between main and secondary joints is, the main joint controls crack propagation and failure of granite specimen, which occurs the shear failure propagating from main joint tips, and the corresponding uniaxial compressive strength is low. Meanwhile, the secondary joint is the key joint for crack propagation and failure at α of 0° and 90° except when β is 90°. The granite specimen occurs the shear failure propagating from secondary joint tips. And, the shear failure crossing upper tips of main and secondary joints is found at α of 0° or 90° and β of 90°. Their uniaxial compressive strengths are large. Also, the combined actions of main and secondary joints determine crack propagation and failure at α of 60° except when β is 90°. The granite specimen occurs the hybrid failure, including shear failure propagating from main joint tips and tensile failure propagating from main and secondary joints center or secondary joint tips. And, when α is 60° and β is 90°, the granite specimen occurs the shear failure along secondary joint plane direction, and its uniaxial compressive strength is small. Generally, when α or β is a fixed value, the uniaxial compressive strength firstly decreases and then increases with the increase of β or α . Additionally, when α is 60° and β > 45 °, the uniaxial compressive strength represents a decreasing trend. The uniaxial compressive strength at α and β between 30° and 60° is generally small. Finally, the microdisplacement field distributions of granite specimen were discussed.